Time‐series response of immune enzymes and catecholamines in juvenile sea cucumber Apostichopus japonicus during long‐term live transport. (12th May 2019) - Xie, Xi; Yang, Miao; Zhang, Libin; Zhang, Tao; Zhou, Zunchun; Wang, Qingzhi; Teng, Weiming; Yang, Hongsheng
Abstract: Sea cucumbers are free of protective exoskeleton and capable of autolysis under stress conditions. The live transport of small‐size juveniles to grown‐out sites induces hypoxia and congesting stress. The transport process is essential to production of outdoor healthy seedlings. Here, we evaluated the effects of damp transport and water transport on Apostichopus japonicus, an economic species inhabiting along the Asian coast. The survival after transport and immune performance of small‐size juveniles (0.05–0.1 g of immersed weight) were monitored during distinct duration of transport (1, 3, 5, 8 and 12 hr). The results revealed that there were no significant differences between the two transport systems within 5 hr. Given the survival for recovery of 48 hr and responses of immune enzymes and catecholamines during transport, water transport was less detrimental to sea cucumbers than damp transport when the transport duration was less than 8 hr. Once the duration prolonged to 12 hr, these immune parameters changed irregularly and the survival declined drastically. Water transport with a notably higher survival for juveniles was the more appropriate manner for long‐time transport. These findings provide insights into long‐term transport of small‐size A.  japonicus juveniles and might be beneficial for production of ecologically healthy seedlings.